Gay App Use, Sexuality Traits, and High-Risk Sexual Behaviors Among Men Who Have Sex With Men in China: Mediation Analysis - Rui Luo; Zhi Xie; Vincent M B Silenzio; Yun Kuang; Dan Luo (JMIR Publications, 2023)
BackgroundGay geosocial networking apps, also known as "gay apps," have gained increasing popularity in the men who have sex with men (MSM) community. Certain sexuality traits and gay app use are both associated with high-risk sexual behaviors among MSM. However, little is known about the underlying mechanism of such relationships. ObjectiveBased on the uses and gratifications theory, this study aimed to test the mediation effect of gay app use on the relationship between sexuality traits (sexual compulsivity and sexual sensation seeking) and high-risk sexual behaviors (multiple sexual partners and unprotected anal intercourse) among MSM. MethodsA cross-sectional, multicenter study was conducted in Wuhan and Changsha, China, from August to October 2020. A representative sample of 402 MSM was recruited through respondent-driven sampling. A self-administered web-based structured questionnaire was used to collect data on sociodemographic information, high-risk sexual behaviors, gay app use, sexual compulsivity, and sexual sensation seeking. Path analysis was conducted to assess the mediation effect. ResultsOur study revealed that 67.42% (n=271) of MSM used gay apps for seeking potential sexual partners, with 37.06% (n=149) of them engaging in unprotected anal intercourse, and 45.42% (n=218) of them having multiple sexual partners. Of the participants, 17.16% (n=69) reported significant sexual compulsivity, while 29.10% (n=117) reported significant sexual sensation seeking. Notably, gay app usage partially mediated the relationship between sexual compulsivity and multiple sexual partners but fully mediated the relationship between sexual compulsivity and unprotected anal intercourse. Furthermore, gay app usage partially mediated the relationship between sexual sensation seeking and multiple sexual partners but fully mediated the relationship between sexual sensation seeking and unprotected anal intercourse. ConclusionsHigh-risk sexual behaviors are common among MSM. Most MSM rely on gay apps to find sexual partners, which, when combined with higher levels of sexual compulsivity and sexual sensation seeking, can increase the likelihood of engaging in high-risk sexual behaviors. Therefore, interventions aimed at reducing these behaviors among MSM should focus on addressing the use of gay apps, while also considering the influence of their sexuality traits on gay app use.